PENGARUH KEPEMILIKAN KELUARGA, KEPEMILIKAN INSTITUSIONAL, DAN KEPUTUSAN PENDANAAN TERHADAP KINERJA KEUANGAN DENGAN METODE PIOTROSKI F-SCORE - David Halim; Sugi Suhartono (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2021)
Financial performance is an achievement achieved by a company that can be seen through financial statements. Financial statements can be used as a control, a source of financial information and a representation of the company's performance. The results of financial statement analysis with various sizes of financial ratios can be used as material for evaluating company performance This study aims to determine the effect of family ownership, institutional ownership, and funding decisions on financial performance as measured by the Piotroski F-Score method. The number of samples in this study were 360 companies from the manufacturing sector with sub-sector basic and chemical industry, various industrial sectors and consumer goods listed on the Indonesia Stock Exchange during the period 2017 - 2019. The results of this study indicate that the data can be pooled for 3 years, all classical assumption tests are met and the results of the regression test show that family ownership > 0.05, institutional ownership and funding decisions < 0.05. So it can be concluded that there is not enough evidence of family ownership to have a positive effect on financial performance. Meanwhile, there is sufficient evidence that institutional ownership and funding decisions have a negative effect on financial performance. Keywords: family ownership, institutional ownership, funding decisions, financial performance and Piotroski F-Score. References: Agatha, B. R., Nurlaela, S., & Samrotun, Y. C. (2020). Kepemilikan Manajerial, Institusional, Dewan Komisaris Independen, Komite Audit dan Kinerja Keuangan Perusahaan Food and Beverage. E-Jurnal Akuntansi, Vol. 30 No. 7, 1811. Aprianingsih, A., & Yushita, A. N. (2016). Pengaruh Penerapan Good Corporate Governance, Struktur Kepemilikan, Dan Ukuran Perusahaan Terhadap Kinerja Keuangan Perbankan. Jurnal Profita, Vol. 4 No. 5, 1–16. Cooper, D., & Schindler, P. (2013). Business Research Methods: 12th Edition. McGraw-Hill Higher Education. Dewi, L. S., & Abundanti, N. (2019). Pengaruh Profitabilitas, Likuiditas, Kepemilikan Institusional Dan Kepemilikan Manajerial Terhadap Nilai Perusahaan. E-Jurnal Manajemen Universitas Udayana, Vol. 8 No. 10, 6099. Dewi, M. M., & Sulasmiyati, S. (2016). Pengaruh Struktur Kepemilikan, Ukuran Perusahaan, dan profitabilitas Terhadap Leverage (Studi pada Perusahaan LQ-45 yang terdaftar di Bursa Efek Indonesia Tahun 2013-2016). Jurnal Administrasi Bisnis (JAB), Vol. 55 No. 1, 27–37. Fadillah, A. R. (2017). Analisis Pengaruh Dewan Komisaris Independen, Kepemilikan Manajerial Dan Kepemilikan Institusional Terhadap Kinerja Perusahaan Yang Terdaftar Di Lq45. Jurnal Akuntansi, Vol. 12 No. 1, 37–52. Fama, E. F., & Jensen, M. C. (1983). Separation Of Ownership And Control. Corporate Governance: Values, Ethics and Leadership, 163–188. Finda Yovita dan Juniarti. (2017). Struktur Kepemilikan Keluarga dan Kinerja Perusahaan pada Sektor Aneka Industri. Business Accounting Review, Vol. 5 No. 2, 445–456. Ghozali, I. (2016). Aplikasi analisis Multivariete dengan program IBM SPSS 23 (edisi 8). Cetakan Ke VIII. Semarang: Badan Penerbit Universitas Diponegoro, 96. Haryono, S. A., Fitriany, F., & Fatima, E. (2017). Pengaruh Struktur Modal Dan Struktur Kepemilikan Terhadap Nilai Perusahaan. Jurnal Akuntansi Dan Keuangan Indonesia, Vol. 14 No. 2, 119–141. Jensen, M. C., & Meckling, W. H. (2019). Theory Of The Firm: Managerial Behavior, Agency Costs And Ownership Structure. Corporate Governance: Values, Ethics and Leadership, 4, 77–132. Kristianti, I. P. (2018). Analisis Pengaruh Struktur Modal. Jurnal UST JOGJA, Vol. 2 No. 1, 56–68. Kusumadewi, A., & Zulhaimi, H. (2019). Pengaruh Kepemilikan Manajerial, Kepemilikan Institusional, Dewan Komisaris, Komite Audit dan Kualitas Audit Terhadap Kinerja Keuangan Perusahaan. Forum Keuangan Dan Bisnis ( FKBI ) VII 2019 Forum Keuangan Dan Bisnis Indonesia ( FKBI ), Vol. 5, 241–256. Latifah, S. W., & Luhur, M. B. (2017). Peran Komisaris Independen Dan Komite Audit Dalam Meningkatkan Kinerja Keuangan Perusahaan Wholesale Dan Retail Trade Di Indonesia. Jurnal Akuntansi Dan Bisnis, Vol. 17, 13–18. Leatemia, E. M., Mangantar, M., Rogi, M. H., Ekonomi, F., Manajemen, J., & Ratulangi, U. S. (2019). Pengaruh Corporate Governance Terhadap Kinerja Keuangan Pada Perusahaan Textile Dan Garmen Yang Terdaftar Di Bursa Efek Indonesia Periode 2013-2017. Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis Dan Akuntansi, Vol. 7 No. 3, 4339–4348. Lestari, P. (2020). Pengaruh Likuiditas, Der, Firm Size, Dan Asset Turnover Terhadap Kinerja Keuangan. Jurnal Neraca: Jurnal Pendidikan Dan Ilmu Ekonomi Akuntansi, Vol. 4 No. 1, 1. Marpa, N. (2012). Perusahaan keluarga sukses atau mati. Tangerang: Penerbit Cergas Media. Mathova, A., Perdana, H. D., & Rahmawati, I. P. (2017). Pengaruh Kepemilikan Keluarga dan Good Corporate Governance Terhadap Kualitas Laba dan Kinerja Perusahaan. SAR (Soedirman Accounting Review) : Journal of Accounting and Business, Vol. 2 No. 1, 73. McConnell, J. J., & Servaes, H. (1990). Additional Evidence On Equity Ownership And Corporate Value. Journal of Financial Economics, Vol. 27 No. 2, 595–612. McGee, T. (2013). Perspectives on family-owned businesses: Governance and succession planning. 1–20. Delloite Growth Enterprise Services Myers, S. C., & Majluf, N. S. (1984). Corporate financing and investment decisions when firms have information that investors do not have. Journal of Financial Economics, Vol. 13 No. 2, 187–221. Piotroski, J. D. (2000). Discussion of Value Investing: The Use of Historical Financial Statement Information to Separate Winners from Losers. Journal of Accounting Research, 38, 43. Pound, J. (1988). Proxy contests and the efficiency of shareholder oversight. Journal of Financial Economics, Vol. 20 (C), 237–265. PrincewaterhouseCoopers Indonesia (PwC). (2014). Survey Bisnis Keluarga 2014. November 2014, November, 1–35. Rahma, A. (2014). Pengaruh Kepemilikan Manajerial, Kepemilikan Institusional, Dan Ukuran Perusahaan Terhadap Keputusan Pendanaan Dan Nilai Perusahaan (Studi Kasus Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2009-2012). Vol. 23 No. 2, 45–69. Sari, R. (2020). Pengaruh Kepemilikan Asing Dan Leverage Terhadap Kinerja Keuangan. Balance : Jurnal Akuntansi Dan Bisnis, Vol. 5 No. 1, 64. Susanti, L. D., & Juniarti. (2017). Pengaruh Struktur Kepemilikan Keluarga Terhadap Kinerja Perusahaan Perusahaan Property dan Real Estate. Business Accounting Review, Vol. 5 No. 2, 709–720. Susanto, A. B., Susanto, P., Wijanarko, H., & Mertosono, S. (2007). The Jakarta consulting group on family business. Jakarta: The Jakarta Consulting Group. Wianta Efendi, A. F., & Adi Wibowo, S. S. (2017). Pengaruh Debt To Equity Ratio (Der) Dan Debt To Asset Ratio (Dar) Terhadap Kinerja Perusahaan Di Sektor Keuangan Yang Terdaftar Di Bursa Efek Indonesia. Journal of Applied Managerial Accounting, Vol. 1 No. 2, 157–163. Wild.Subramanyam. (2010). Analisis Laporan Keuangan, Financial Statement Analysis. Analisis Laporan Keuangan, Financial Statement Analysis, Edisi Ke Sepuluh: Salemba Empat, Jakarta, Vol. 4 No. 2, 265–276. Yudha, D. P., & Singapurwoko, A. (2017). The Effect Of Family And Internal Control On Family Firm Performance: Evidence From Indonesia Stock Exchange (IDX). Journal of Business and Retail Management Research, Vol. 11 No. 4, 68–75.